Comparison of ultrasound and UV technologies to control bulking and foaming in a wastewater treatment facility. A case study in an industrial park in Morelos, Mexico - Hernández-Romano, Jesús; Trevino-Quintanilla, Luis; Guillén-Garcés, Angélica; Barragán-Trinidad, Martín; Bustos-Terrones, Victoria; Díaz de Anda, Diana K.; Moeller-Chávez, Gabriela (Frontiers in Environmental Science, 2022)
The paper aimed to study the effect of the application of low-frequency ultrasound technology and UV application on the disintegration of filamentous organisms when they are present in the mixed liquor tank of an activated sludge wastewater treatment plant. Some bench-scale experiments were performed using the bulked sludge from the secondary clarifier in an industrial park (CIVAC) in Morelos, Mexico, affected by filamentous organisms causing operational problems like lack of settleability and higher suspended solids content in the effluent. We proposed the use of an ultrasonic device and the application of UV radiation to control the filaments forming situation without the risk of by-products formation that could adversely affect health issues if for example chlorine is added. Secondary sludge mixed liquor was used and exposed to UV application and ultrasound treatment. For the UV experiments, a UV irradiation lamp was employed with a 254 wavelength, and applying two, four, and six minutes irradiation times. A 20kHz frequency, 35% amplitude, and an ultrasonic density of 3333.3 W/L were used for the ultrasound treatment. Sonication times used were: 5 and 10 minutes without control of temperature. Results showed that for the UV application for 2, 4, and six minutes, the settleability of the mixed liquor suspended solids was not improved; on the other hand, the cavitation effect caused by the ultrasound application demonstrated effective action against the destruction of filamentous organisms. The 10 minutes condition showed a significant decrease in the filament integrity of the microorganisms and a significant improvement of sedimentation and sludge volume index (SVI) values and settleability of the sludge, but not enough, to satisfy national discharge regulations related to total suspended solids in the treated effluent. Molecular identification indicates the presence of the genera Thauera and Brevundimonas as predominant in the filamentous sludge.